Pengembangan Sistem Informasi Personal Finance Management Menggunakan Pendekatan Rapid Application Development - Pahlevi, Omar; Amrin; Handrianto, Yopi (STMIK Budi Darma, 2024)
In the increasingly advanced digital era, many individuals struggle to manage their personal finances efficiently, often resulting in financial problems such as accumulating debt and the inability to save consistently. This issue is exacerbated by manual financial record-keeping, which is prone to errors and inefficient in providing a comprehensive and real-time financial overview. This study aims to develop and evaluate a personal finance management information system using the Rapid Application Development (RAD) approach. The RAD method was chosen for its iterative and flexible approach, allowing for quick adjustments according to user needs. This study also includes system evaluation through usability testing to measure efficiency, effectiveness, and user satisfaction. The results show that the application of RAD successfully produced high-quality software within three months, featuring key functionalities for managing income and expense data, as well as displaying financial reports based on specific periods. Additionally, usability testing indicated an average score of 87.5%, which falls into the 'Good' category, confirming the system's operational readiness and usability for users.